Economic growth, convergence, and agricultural economics - Martin, Will (John Wiley & Sons, 2019)
After nearly two centuries of lagging behind the industrial countries, growth in many developing countries has surged since the early 1990s. This outperformance has major implications for almost all areas of agricultural economics and, if continued, will likely do so into the future. This article aims to identify the key ways in which the changes in rich and poor country growth rates matter for agricultural economists, as a basis for formulating better research agendas. A key impact arises through sharp increases in demand for agricultural resources as demand for livestock products increases. This changing structure of food demand has important implications for nutrition studies and policies, with the emergence of a double burden of malnutrition. On the supply side, growth in developing countries tends to increase domestic food supply, which is also boosted by increases in research and development spending. Growth in developing countries both stimulates and benefits from increases in infrastructure investment, evaluation of which requires new analytical tools. Negative impacts include the contribution of increased demand for livestock products to global greenhouse gas emissions. In terms of trade policy, growth in developing country is tending to lead to convergence of agricultural policies with the pattern of assistance seen in today's developed countries, raising concerns about the future need to deal with collective action problems, particularly those that increase the volatility of world prices.